Permo-Triassic salt provinces of Europe, North Africa and the Atlantic margins tectonics and hydrocarbon potential - Soto, Juan I.; Flinch, Joan F.; Tari, G. C. (Amsterdam Elsevier, 2017)
Permo-Triassic Salt Provinces of Europe, North Africa and the Atlantic Margins: Tectonics and Hydrocarbon Potential deals with the evolution and tectonic significance of the Triassic evaporite rocks in the Alpine orogenic system and the Neogene basins in the Iberian Peninsula, North Africa, and the western Mediterranean. As the nature of the Triassic evaporite sequences, the varied diapiric structures they feed, and the occurrence of hydrocarbons suggest that the Triassic evaporites represent an efficient system to trap hydrocarbons, this book explores the topic with a wide swath, also devoting content to a relatively unexplored topic, the mobilization and deformation of the Triassic salt in the western and northern Tethys (from Iberia and North Africa, Pyrenees and Alps, Adriatic and Ionian) during the subsequent Alpine orogenic processes. The book includes chapters updating varied topics, like the Permian and Triassic chronostratigraphic scales, palaeogeographic reconstructions of the western Tethys since the Late Permian, the petroleum systems associated with Permo-Triassic salt, allochthonous salt tectonics, and a latest revision of salt tectonic processes in the Permian Zechstein Basin, the Atlantic Margins (from Barents Sea, Scotia, Portugal, Morocco, and Mauritania), the Alpine folded belts in Europe, and the various Triassic salt provinces in North Africa. The book is the go-to guide for salt tectonic researchers and those working in the hydrocarbon exploration industry.--Provided by publisher.
Salt tectonics in time and space. Permo-Triassic basins and tectonics in Europe, North Africa and the Atlantic margins : a synthesis / J.I. Soto, J.F. Flinch, G. Tari -- The Permian and Triassic chronostratigraphic scales : framework for ordering events / S.G. Lucas -- Late Permian-Early Jurassic paleogeography of western Tethys and the world / C.R. Scotese, A. Schettino -- An overview of Allochthonous salt tectonics / M.G. Rowan -- The internal structure of the Zechstein salt and related drilling risks in the northern Netherlands / F. Strozyk -- Petroleum systems and play types associated with Permo-Triassic salt in Europe, North Africa and the Atlantic region / G. Tari, J.F. Flinch, J.I. Soto -- Zechstein Basin. Paleogeographic evolution of latest Permian and Triassic salt basins in northwest Europe / T. McKie -- Composition, tectonics, and hydrocarbon significance of Zechstein supergroup salt on the United Kingdom and Norwegian continental shelves : a review / C.A.-L. Jackson, S.A. Stewart -- Structure and evolution of the Glueckstadt Graben in relation to the other postPermian subbasins of the central European basin system / Y.P. Maystrenko, U. Bayer, M. Scheck-Wenderoth -- The tectonic history of the Zechstein Basin in the Netherlands and Germany / F. Strozyk, L. Reuning, M. Scheck-Wenderoth, D.C. Tanner -- Permo-Triassic evaporites of the Polish Basin and their bearing on the tectonic evolution and hydrocarbon system, an overview / P. Krzywiec, T.M. Peryt, H. Kiersnowski, P. Pomianowski, G. Czapowski, K. Kwolek -- Atlantic margins. Salt tectonics of the Norwegian Barents Sea and northeast Greenland shelf / M.G. Rowan, S. Lindsø -- A review of Mesozoic-Cenozoic salt tectonics along the Scotian margin, eastern Canada / M.E. Deptuck, K.L. Kendell -- Influence of salt diapirism on the basin architecture and hydrocarbon prospects of the western Iberian margin / R. Pena dos Reis, N. Pimentel R. Fainstein, M. Reis, B. Rasmussen -- Salt tectonics along the Atlantic margin of NW Africa (Morocco and Mauritania) / G. Tari, B. Novotny, H. Jabour, M. Hafid -- Salt tectonics within the offshore Asturian Basin : north Iberian margin / G. Zamora, M. Fleming, J. Gallastegui --- Alpine folded belts. Salt and strike-slip tectonics as main drivers in the structural evolution of the Basque-Cantabrian basin, Spain / P. Cámara -- The southern Pyrenees : a salt-based fold-and-thrust belt / P. Cámara, J.F. Flinch -- Allochthonous Triassic and salt tectonic processes in the Betic-Rif orogenic arc / J.F. Flinch, J.I. Soto -- The role of the Triassic evaporites underneath the north Alpine foreland / A. Sommaruga, J. Mosar, M. Schori, M. Gruber -- The eastern Alps : multistage development of extremely deformed evaporites / C. Leitner, C. Spötl -- Salt tectonics in the Carnian evaporite basin of the eastern Balkan-Forebalkan region of Bulgaria / G. Georgiev, G. Tari -- The Triassic evaporites in the evolution of the Adriatic basin / V. Scisciani, P. Esestime -- The Ionian fold-and-thrust belt in central and southern Albania : a petroleum province with Triassic evaporites / Z. Bega, J.I. Soto -- North Africa. Styles of salt tectonics in central Tunisia : an overview / H. Troudi, G. Tari, W. Alouani, G. Cantarella -- Salt tectonics in the Atlas Mountains of Morocco / J. Vergés, M. Moragas, J.D. Martín-Martín, E. Saura, E. Casciello, Ph. Razin, C. Grelaud, M. Malaval, R. Joussiame, G. Messager, I. Sharp, D.W. Hunt -- Development of an Upper Triassic-Lower Jurassic evaporite basin on the Saharan platform, North Africa / P. Turner, K. Pelz.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Salt deposits -- Europe; Salt deposits -- Africa, North; Salt deposits -- Atlantic Ocean Region; Hydrocarbon reservoirs -- Europe; Hydrocarbon reservoirs -- Africa, North; Hydrocarbon reservoirs -- Atlantic Ocean Region; Electronic books